Steroid resistant focal segmental glomerulosclerosis: effect of arterial hyalinosis on outcome: single center study - Soliman Amin R.; Maamoun Hoda; Soliman Haytham; Ahmed Rabab Mahmoud (Sciendo, 2021)
Background. Few data with adequate evidence exists as regards the effect of Cyclosporine (CsA) and mycophenolate mofetil (MMF) on pathological prognostic parameters in patients with steroid resistant focal segmental glomerulosclerosis (FSGS). The purpose of the present study is to compare the effect of cyclosporin and mycophenolate mofetil in addition to steroids on functional and histopathologic renal parameters in patients with steroid resistant FSGS one year after treatment.